1986
DOI: 10.1093/clinchem/32.10.1797
|View full text |Cite
|
Sign up to set email alerts
|

The chemistry of aluminum as related to biology and medicine.

Abstract: The increasing number of roles discovered for Al3+ in physiological processes demands an understanding of how Al3+ interacts with compounds in biological systems. Al3+ is expected to complex with oxygen donor ligands, especially phosphates, and it does so in soils, in the gastrointestinal tract, and in cells. The stability of Al3+ complexes has generally been misjudged because of lack of recognition that free, aqueous Al3+ is not the dominant form in neutral solutions and that the solubility of Al(OH)3 limits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
195
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 570 publications
(200 citation statements)
references
References 0 publications
5
195
0
Order By: Relevance
“…Saturation values of soluble aluminium hydroxides in a neutral aqueous solution are presumably very low: 8 x 10-6M for Al(OH)and 10-"M for Al(H2O)6+ (MacDonald & Martin, 1988). Several recent publications indicate that the trivalent cation is the biotoxic form of this substance (Martin, 1986;Birchall & Chappell, 1988). Never-g 50o Q.…”
Section: Activity Recordingmentioning
confidence: 99%
“…Saturation values of soluble aluminium hydroxides in a neutral aqueous solution are presumably very low: 8 x 10-6M for Al(OH)and 10-"M for Al(H2O)6+ (MacDonald & Martin, 1988). Several recent publications indicate that the trivalent cation is the biotoxic form of this substance (Martin, 1986;Birchall & Chappell, 1988). Never-g 50o Q.…”
Section: Activity Recordingmentioning
confidence: 99%
“…A particular problem in the production of homogeneously loaded aluminium standards is the extremely limited solubility of aluminium salts at neutral pH, since at this pH precipitation of AI (OH) 3 occurs. In order to achieve a homogeneous distribution of aluminium it was necessary to use an acidic pH [20]. Preliminary experiments have shown that in aluminium loaded, acidified brain tissue homogenates, a uniform distribution of aluminium was present both in ion images and depth profiles recorded from each homogenate.…”
Section: Discussionmentioning
confidence: 99%
“…Aluminium salts (sodium and potassium sulphate) have been evaluated by JECFA in 1978(JECFA, 1978 that concluded that the use of aluminium metal as a silvering decoration for certain items of confectionary was not considered to present a health hazard. SALP (E 541) was evaluated by JECFA in 1982, 1985, 1986, 1988, 2006(JECFA, 1982, 1986, 1987, 1989, 2007. In its first evaluation in 1982, a temporary acceptable daily intake (ADI) of 0-6 mg/kg body weight (bw) was allocated due to insufficient data.…”
Section: Information On Existing Authorisations and Evaluationsmentioning
confidence: 99%